Personality factors influencing intention on cash waqf behavior - Mohd Zain, Nor Hazila; Muda, Muhamad; Rosman, Romzie (Zes Rokman Resources, 2019)
The issue of donation has received great attention around the world. According to Cheung & Chan, (2000) the public donation significantly contribute toward helping the poor and needy people living across the globe. Currently, waqf also can be recognized as one of the potential investment instruments which can be developed to fund various economic activities for the benefit of community (Hasan & Abdullah, 2008). Cash waqf is a trust fund established with money to support services to mankind in the name of Allah. Cash waqf development in Malaysia is rapidly growing in the last decade, leading a good understanding of donator perceptions is important for the waqf authority to improve the waqf system and consequently encourage people compliance waqf. The study was conducted through survey questionnaire among respondents in Malaysia. A number of 345 valid questionnaires had been analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The study found that only conscientiousness was significant to intention on cash waqf. Agreeableness has significance difference but the hypothesis unsupported due to both of this factor hypothesized as positive relationship with intention.